Pengelolaan piutang pajak bumi dan bangunan perdesaan dan perkotaan pasca peralihan di Kabupaten Katingan - Afni Nooraini; Christian Anugrah Pratama; Marja Sinurat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The government has transferred the Rural and Urban Land and Building Tax from the central tax to a regional tax to provide additional sources of income for regional development, however, after the transition, there was an increase in PBB-P2 receivables. This study aims to analyze the management of PBB-P2 receivables, analyze factors affecting highly PBB-P2 receivables and analyze the efforts of Katingan Regency Government to reduce PBB-P2 receivables. This study uses a descriptive qualitative research method with an inductive approach. Data collection techniques through interviews and documentation. Sampling was done by purposive sampling method with 11 informants. This study concludes that the management of PBB-P2 receivables in Katingan Regency has not been carried out properly. The increase in PBB-P2 receivables in Katingan Regency is due to the lack of updating of tax subject and object data, lack of competence of tax management apparatus, lack of socialization for the community, and low public awareness of paying taxes. Various efforts have been made by BPKAD Katingan Regency, namely making PBB-P2 data collection applications, not printing Tax Returns Payable for people who have receivables, and collecting taxpayers who are no longer domiciled in Katingan Regency.